Editorial Commentary: Science for All: Boosting knowledge through communication - Kazembe, Lawrence; Kangira, Jairos (Namibian Journal for Research, Science and Technology, 2022)
Excellence is an art won by training and habituation* - Aristotle The need for science, technology, engineering and mathematics (STEM) to spearhead development has increased steadily, while communication and dissemination fall behind. In a world continuously influenced by scientific development, STEM communication grows ever more important to enable active engagement and participation of citizens in society. The intention is to engage society to increasingly recognize and illustrate the important of STEM for daily life, while boosting science motivation among students to learn STEM subjects, thus creating a critical mass of scientists, engineers and technologists for the world's tomorrow. This need is even more of a challenge in developing countries, like Namibia, where there is limited funding towards STEM. Since 2015, the National Commission for Research, Science and Technology, in Namibia, has engaged in science fairs, public talks, or participatory projects, including publications as channels on reaching and engaging underserved audiences of STEM. One such publication is this journal. Now in its fourth volume, a special collection of articles on applications of statistics is showcased in this journal issue. The articles, edited by Dr Opeoluwa Oyedele, a senior lecturer in the Department of Computing, Mathematical and Statistical Sciences - formerly Department of Statistics and Population Studies, in the School of Science, are drawn from a selection of research done by postgraduate students and staff in that department. The collection tries to showcase the breath to which statistical techniques and methods are applied in a real world. All case studies are drawn from the Namibian context. The list of the articles is: • Statistics: an intrinsic part of everyday life - commentary • Modelling state preferences among airline travellers in Namibia: a case study at Eros airport and Hosea Kutako international airport • Zero-augmented models for exploring the factors affecting the pass rate of 2016 grade 10 learners in Khomas region, Namibia • Assessing the impact of proximate and non-proximate determinants of fertility in Namibia: a structural equation modelling approach • Household poverty levels in Namibia and their associated sociodemographic factors: An empirical investigation of the 2015/16 Namibia household income and expenditure survey • An application of survival analysis on the determinants of employment longevity in Namibia: evidence from 2018 Labour Force Survey • Customer relationship management (CRM) and passenger loyalty in delivering high quality service at Air Namibia: A structural equations approach • Application of longitudinal analysis to crime Data: Windhoek case study {2011-2016) • Socio-demographic variations on age-sex mortality in Namibia: an analysis of the 2016 civil registration and vital statistics data • A logistic regression model to assess factors influencing schizophrenia symptoms in Namibia • An ecological adjusted random effect model for property crime in Windhoek, Namibia {2011-2016) This collection is the first of its kind, and we look forward to many more, in line with the four main goals of NJRST, which is to inform, innovate, educate and debate, hence boosting scientific communication. We invite our readers to appreciate the beauty of statistics as presented here.